Expression and purification of RHC–EGFP fusion protein and its application in hyaluronic acid assay. Issue 3 (16th March 2017) - Duan, Ningjun; Lv, Wansheng; Zhu, Lingli; Zheng, Weijuan; Hua, Zichun
ABSTRACT: Hyaluronan is a widely distributed glycosaminoglycan which has multiple functions. Hyaluronic acid (HA) accumulation has been reported in many human diseases. Understanding the role of hyaluronan and its binding proteins in the pathobiology of disease will facilitate the development of novel therapeutics for many critical diseases. Current techniques described for the analysis of HA are mainly for HA quantification in solutions, not for the direct detection of HA in tissues or on cell surfaces. In our study, a fusion protein, named C-terminal domain of RHAMM–enhanced green fluorescence protein (RHC–EGFP), combined the HA-binding domain, C-terminal of receptor for hyaluronan-mediated motility, with EGFP, a widely used enhanced green fluorescence protein, was expressed and purified from Escherichia coli with high purity. Based on the sensitivity and convenience of fluorescence detection, methods for direct assay of HA in solutions, on cell surface or in tissues were established using RHC–EGFP. The binding specificity was also confirmed by competitive binding experiment and hyaluronidase degradation experiment. Our results provide an alternative choice for the specific and convenient assay of HA in various samples, and maybe helpful for further understanding of the fundamental and comprehensive functions of HA.